The Effect of Digital Service Quality and Customer Trust on Shopee E-Commerce Customer Loyalty in Cirebon - Armando Armando; Revanza Rizky Ramadhan (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid development of digital technology has driven significant changes in consumer behavior, particularly through e-commerce platforms. Shopee, as one of Indonesia's leading e-commerce platforms, continues to improve its service quality and build trust to maintain customer loyalty. This study aims to analyze the influence of digital service quality and customer trust on Shopee user loyalty in Cirebon. The method used was a quantitative survey approach, involving 135 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. Validity, reliability, normality, heteroscedasticity, t-test, F-test, and coefficient of determination tests were conducted to ensure the validity of the research model. The study's results indicate that both digital service quality and customer trust have a positive and significant impact on customer loyalty. Together, these two variables explain 59.7% of the variability in customer loyalty. These findings suggest that enhancing digital service quality and fostering trust are crucial strategies for Shopee in maintaining customer loyalty amid increasingly competitive e-commerce environments.